2017
DOI: 10.1177/0271678x17695572
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and metalloproteinases profiles predict three-month poor outcomes in ischemic stroke treated with thrombolysis

Abstract: Inflammatory mediators and metalloproteinases are altered in acute ischemic stroke (AIS) and play a detrimental effect on clinical severity and hemorrhagic transformation of the ischemic brain lesion. Using data from the Italian multicenter observational MAGIC (MArker bioloGici nell'Ictus Cerebrale) Study, we evaluated the effect of inflammatory and metalloproteinases profiles on three-month functional outcome, hemorrhagic transformation and mortality in 327 patients with AIS treated with intravenous thromboly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 33 publications
0
42
0
Order By: Relevance
“…Nezu et al [13] identified alpha-2-macroglobulin as an acute IS biomarker, and Gori et al [22] found that this protein was significantly associated with poor outcome (death within three months), suggesting that it contributes to cerebral damage after IS and thrombolysis. The authors conclude that high levels of alpha-2-macroglobulin may be a useful prognostic biomarker to identify patients with an increased probability of death after the administration of tissue plasminogen activator [22].…”
Section: Discussionmentioning
confidence: 99%
“…Nezu et al [13] identified alpha-2-macroglobulin as an acute IS biomarker, and Gori et al [22] found that this protein was significantly associated with poor outcome (death within three months), suggesting that it contributes to cerebral damage after IS and thrombolysis. The authors conclude that high levels of alpha-2-macroglobulin may be a useful prognostic biomarker to identify patients with an increased probability of death after the administration of tissue plasminogen activator [22].…”
Section: Discussionmentioning
confidence: 99%
“…Under normal condition, the expression of MMPs in the brain is very low. Ischemic stroke may induce increased expression of MMPs, especially MMP9 . Both brain vascular ECs and infiltrating neutrophils can produce MMP9 after focal cerebral ischemia, which can be used to predict stroke patient outcome .…”
Section: The Double‐faced Roles Of Peripheral Immune Activation On Thmentioning
confidence: 99%
“…Ischemic stroke may induce increased expression of MMPs, especially MMP9 . Both brain vascular ECs and infiltrating neutrophils can produce MMP9 after focal cerebral ischemia, which can be used to predict stroke patient outcome . In ischemic stroke patients, MMP9 increases in the plasma within the first 2 to 6 hours and the MMP9 mRNA in leukocytes increased within 3 hours Activated neutrophils may be an important source of pre‐existing intracellular MMP9 pool, which can be secreted in response to middle cerebral artery occlusion (MCAO) and oxygen‐glucose deprivation (OGD) insults In addition, activated MMPs may also be triggered by increased TNF‐ α, IL‐6, and α2‐antiplasmin in the blood The granulocyte‐colony stimulating factor (G‐CSF) can stimulate the proliferation of peripheral neutrophils and thus increase the level of MMP9, leading to exacerbated BBB disruption and increased ischemic infarction …”
Section: The Double‐faced Roles Of Peripheral Immune Activation On Thmentioning
confidence: 99%
“…The latest guideline of acute stroke treatment still recommends tPA as the first‐line of effective thrombolytic treatment to achieve early reperfusion of the ischemic brain . However, the current therapeutic window of 4.5 hours after the onset of stroke remarkably limits the clinical use of tPA thrombolysis . BBB disruption is a fundamental pathological feature of intracerebral HT induced by tPA thrombolysis .…”
Section: Discussionmentioning
confidence: 99%
“…2,3,30 However, the current therapeutic window of 4.5 hours after the onset of stroke remarkably limits the clinical use of tPA thrombolysis. [31][32][33] BBB disruption is a fundamental pathological feature of intracerebral HT induced by tPA thrombolysis. 34,35 Loss of BBB integrity results in increased vascular permeability and is associated with reduced cerebral blood flow and impaired hemodynamic responses.…”
Section: Discussionmentioning
confidence: 99%